Decision Support System For Selection Of The Best Doctors In Sari Mutiara Hospital Using Fuzzy Tsukamoto Method - Ernita Situmorang; Fristi Rindari (Institute of Computer Science (IOCS), 2019)
The doctor is one of the most important things that works to improve sick people. This research proposes to discuss and build a decision system for the selection of the best doctors that can help the selection of the best obgyn doctors using the Fuzzy Tsukamoto method by outlining the code of ethics for medicine, education, service systems, and years of service. The Tsukamoto method is a method that uses membership functions. With this method the optimal solution is sought from certain alternatives and suggestions. In this study, the study conducted research in the Sari Mutiara Lubuk Hospital so that it chose the best doctor on target.